Individualized supplement of water-soluble vitamins: the influence of inflammation and renal function on circulating concentrations in critically digestive disease patients - Wang, Jingjing; Yan, Jing; Chen, Qi; Shi, Linlin; Wang, Ying; Tian, Xiaoxiao; Qi, Yumei; Li, Guoxun; Cao, Hailong (Frontiers in Immunology, 2025)
BackgroundExisting studies have shown the association of circulating vitamin and disease outcome. The study aimed to elucidate individual response of plasma water-soluble vitamins after supplement by PN in critically digestive disorder patients.MethodsWe measured the plasma levels of nine water-soluble vitamins (i.e., C, B1, B2, B3, B5, B6, B7, B9, and B12) in consecutive 478 hospitalized critically digestive disease patients receiving identical vitamin-supplemented by PN. Univariate and multifactorial logistic regression analysis were used to evaluated vitamins deficiency and accumulation. The receiver operating characteristic (ROC) curves were used to predict vitamin abnormalities. Furthermore, restricted cubic spline (RCS) was used to analyze the National Health and Nutrition Examination Survey (NHANES) database (2003-2020). Additionally, plasma vitamins levels were contrastive analyzed after PN.ResultsThere were high prevalence of vitamin C and B9 deficiency (79.71% and 78.45%) but vitamin B2, B5, and B6 accumulation (34.52%, 12.13%, and 11.09%). Multivariate logistic regression analysis revealed that inflammation is an independent risk factor for vitamin C and B9 deficiency, whereas renal dysfunction is an independent risk factor for vitamin B2, B5, and B6 accumulation. The areas under the ROC curves predicting vitamin C, B9 deficiency and vitamin B2, B5, B6 accumulation were 0.80, 0.75, 0.69, 0.79, and 0.89, respectively. The NHANES database further confirms our conclusion. Conventional vitamin supplementation may not efficiently alleviate vitamin C and B9 deficiency in patients with high inflammation, however, it may accelerate plasma vitamin B2, B5, and B6 accumulation with renal dysfunction.ConclusionWater-soluble vitamin levels were associated with inflammation and renal function. For high inflammation, vitamin C and B9 doses may need to exceed standard levels. In renal impairment, avoid indiscriminate B2, B5, and B6 use; if needed, use alternate-day dosing or lower doses.